Solubility enhancement of curcumin utilizing a suitable solubility enhancer: thermodynamics and solute solvent interaction / Norhaziland @ Fatin Mohd @ Mohd Zaid - Mohd @ Mohd Zaid, Norhaziland @ Fatin (2014)
Curcumin is a hydrophobic polyphenolic compound derived from the rhizome of herb Curcuma longa. It has been reported for wide array of pharmacological effect such as anti-inflammatory, antioxidant, anti-diabetic, wound healing and anti-cancer activities. In spite of its major pharmacological significance, curcumin (CMN) suffers with poor solubility. Many attempts are made to improve the CMN solubility and hence its dissolution to achieve better absorption and bioavailability. Arginine (ARG) is an amino acid, which is reported for its activity related to the suppression of protein aggregation and solubility enhancement of poorly soluble compound. In this research, we studied the enhanced solubility of CMN in presence of the cosolute ARG. The results of the solubility measurements of CMN in different test solutions containing ARG increased significantly in concentration dependent manner as evidence by a 330 fold increase in CMN solubility. Besides the solubility, the study intended to resolve the thermodynamics that is responsible for the solubility enhancement as a result of better solute and solvent interaction. Therefore, thermodynamic parameters for the solubility enhancement of CMN in presence of ARG have been calculated by using volumetric, conductometric and ultrasonic studies. Volumetric, density and ultrasonic values of both different molar solution of ARG and CMN solubilised in similar solution ARG - CMN have been determined in water with different concentrations (0.05- 0.6 M) at temperature of 298.15, 303.15,308.15 and 313.15K. The conductance values have been used to evaluate the limiting molar conductance (Aom) and the activation energy (Es). From the density values, the limiting partial molar volume and expansibilities have been calculated. However, ultrasonic velocity values of both ARG and ARG- CMN have been determined in water maintaining different concentration at only one temperature 298.15 K. Values of sound velocity have been used to evaluate the parameters such as isentropic compressibility (Ks), apparent isentropic molar compressibility (1C.,), internal pressure (tt,), relative association (Ra), acoustic impedance (Z) and free volume (V/). The compressibility values are observed to increase with increase in solute concentration. All these calculated parameters have been discussed in term of solute (CMN), solvent (water) interactions in presence of ARG. Further the solution state characterizations are done using UV visible and NMR spectroscopy that indicated the formation of a complex. The complex of ARG - CMN has been synthesized successfully by the method of freeze drying. The synthesized complex was further characterized using the solid state characterization tools such as of DSC, FTIR, XRD and FESEM